Wind speed variability and wind power potential over Turkey: Case studies for Canakkale and Istanbul - AKKOYUNLU, BÜLENT OKTAY; TAYANÇ, METE (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, variability of wind speed and its effects on power generation for the 1980-2013 period over Turkey was studied. Hourly wind speed data of 335 stations was obtained from Turkish State Meteorological Service and subjected to quality control. 77 station data was found reliable and used in this work. For the 1980-2013 period, highest hourly average wind speed values equal or larger than 3.80 m/s were found in Gokceada, Canakkale and Mardin stations located at Aegean, Marmara and Southeastern regions of Turkey. Monthly average wind speed is observed to be the highest in July with a value of 2.22 m/s. As an Automated Weather Observation System (AWOS), highest average wind speed for the 2007-2013 period was found in Catalca-Radar, Istanbul with a value of 7.08 m/s. Wind power was analyzed by Weibull distribution and seasonal power density analysis of Canakkale reveals spring, summer and autumn seasonal average power densities as 49.11 W/m(2), 51.12 W/m(2) and 50.16 W/m(2), together with a winter maximum of 81.68 W/m(2). According to results, Catalca was found as the largest wind energy potential in Turkey, not just having the largest wind speed but also having large rural districts for possible wind farm installment. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Renewable energy; Wind speed and potential; Weibull distribution; ELECTRICITY-GENERATION; WEIBULL DISTRIBUTION; ENERGY ANALYSIS; PARAMETERS; MODELS